PENGEMBANGAN E-LKPD MENGGUNAKAN APLIKASI WIZER.ME PADA MATERI INDONESIAKU KAYA ALAMNYA - Alma Sekar Latifah; Surti Kurniasih; Wawan Syahiril (STKIP Subang, 2025)
This research is a Research andDevelopment research. ADDIE (Analysis, Design, Development,Implementation, Evaluation) development model. This research aims todevelop E-LKPD using a Wizer.me application about Indonesiaku KayaAlamnya. This research was carried out at SDN Bojong Nangka 04, in theeven semester of the 2024/2025 school year. In this study, a validationtest was carried out on E-LKPD products by media, language, andmaterial experts. The results of validation by media experts obtained 100%with very feasible criteria, linguists obtained 98% with very feasible criteria,and by material experts 92% with very feasible criteria. The results of thestudent response questionnaire were 91% with very good criteria. Theseresults show that E-LKPD uses an application Wizer.me is very suitable foruse in the learning process and is able to improve student learningoutcomes.